Anoxic-Aerobic Stabilization of Settled Activated Sludge from A Sew Age Treatment Plant - Hii, Siew Ling (2001)
Conventional aerobic sludge stabilization is a power-intensive process. Another major upset is the resulting drop in mixed liquor pH (MLpH). Furthermore, the high concentration of ammonical nitrogen CN"H4-N) , nitrate nitrogen (N03-N), nitrite nitrogen (N02-N) and ortho-phosphate (P04-P) in the filtrate, could be a strong water-polluting agent. In this study, the anoxic-aerobic stabilization system incorporates, at regular intervals, non-aerated periods during aerobic stabilization. Four different stabilization modes (anoxic-aerobic, anoxic-aerobic with methanol, aerobic with lime control and aerobic) were applied to remove both the mixed liquor volatile suspended solids (MLVSS) and soluble nutrients simultaneously. Both the anoxic-aerobic systems were found to have higher solids decay rate, i.e., 0.064 dai1 and 0.057 dai1, respectively, as compared with lime-controlled (0.049 day-I) and aerobic systems (0.033 day-I). Anoxic-aerobic stabilization also maintained neutral MLpH levels at 'no cost', which is superior to daily lime dosing. The unfavorable environment within the aerobic digester (pH 5.51 - pH 6.59) is believed to retard the endogenous metabolisms of the sludge. The aerobic digester showed a significantly high build-up of NH4-N (95% higher) but lower concentrations in both anoxic-aerobic and lime-controlled systems. Since both the anoxic-aerobic digesters experienced anoxic conditions on a regular basis, the peak nitrate were much lower (2.6 mg/L in anoxic-aerobic digester and 1.4 mg/L in anoxic-aerobic digester with methanol). The addition of methanol did accelerate the denitrification process. In contrast, nitrate levels in the lime-controlled digester and aerobic digester were greater than 30.0 mg/L, which do not comply with the World Health Organization standards. Since P04-P is not lost from the digester as gas, the concentration in the four digesters increased with digestion time. The lowest P04-P levels in the lime-controlled digester could be a function of calcium phosphate fonnation. In contrast, the highest level of P04-P in the fully aerobic digester was due to the low MLpH. Alkalinity was consumed and produced during the anoxic-aerobic stabilization process, thus, there was no net change in the alkalinity level. The experimental results indicate that the anoxic-aerobic digestion system is definitely a suitable method for the stabilization of sludge, in terms of solids reduction and soluble nutrients removal.